The great mouse race ebook - Stilton, Geronimo (Geronimo Stilton: Cavemice, 2014)
Geronimo Stilton's ancient ancestor Geronimo Stiltonoot is back in another prehistoric adventure! It's time for the Stone Age Games, the annual cavemouse sports competition! This year, the saber-toothed tigers want to enter the games, too, so they call a truce. But when their flag goes missing, Tiger Khan blames the cavemice! Can Geronimo track it down in time to keep his fur intact?